Analysis of Village Direct Cash Assistance Transfer Payments in Asahan District North Sumatera - Hafni, Roswita; Fadli, Hafiz (AIBPM Publisher, 2023)
The impact of the Covid-19 pandemic on the national economy is carried out by taking fiscal and monetary policies to allocate State Budget (APBN) funds for economic recovery. The purpose of this study was to evaluate the benefits of Direct Cash Transfer (BLT) and Village Cash Intensive Labor in Asahan Regency, North Sumatra. The data used in this study are primary and secondary data, with descriptive analysis techniques. The realization of the Village Fund is a follow-up to the government's program to develop and strengthen regions and villages aimed at improving welfare and equitable development through improving public services, advancing the economy, overcoming development gaps between villages and strengthening communities as subjects of development. In the pandemic era, economic growth has decreased, thus affecting the household economy. Village Fund Cash Transfer and Village Cash Intensive Assistance are assistance in the form of money and work to beneficiary families in the Village sourced from Village Funds to reduce the impact of the Covid-19 pandemic